2004
DOI: 10.1098/rspb.2003.2648
|View full text |Cite
|
Sign up to set email alerts
|

Coping with divided attention: the advantage of familiarity

Abstract: The ability of an animal to perform a task successfully is limited by the amount of attention being simultaneously focused on other activities. One way in which individuals might reduce the cost of divided attention is by preferentially focusing on the most beneficial tasks. In territorial animals where aggression is lower among familiar individuals, the decision to associate preferentially with familiar conspecifics may therefore confer advantages by allowing attention to be switched from aggression to predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
142
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(151 citation statements)
references
References 36 publications
7
142
1
1
Order By: Relevance
“…In a previous study (Brockmark & Johnsson 2010), we suggested that high-density environments may constrain the ability to establish social-based recognition, and coordinate behavioural interactions with specific individuals (Griffiths 2003;Griffiths et al 2004). The sensory overload in a crowded environment (Dukas 2002), together with the associated spatial restriction of activity (Ruxton 1995) and perception may in fact constrain the development of both social and individual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study (Brockmark & Johnsson 2010), we suggested that high-density environments may constrain the ability to establish social-based recognition, and coordinate behavioural interactions with specific individuals (Griffiths 2003;Griffiths et al 2004). The sensory overload in a crowded environment (Dukas 2002), together with the associated spatial restriction of activity (Ruxton 1995) and perception may in fact constrain the development of both social and individual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…feeding) rather than dividing their attention across several tasks (e.g. aggression and feeding) (Griffiths et al 2004). When the horses were tested with familiar persons the difference between the horses' performance in the squatting and standing situations compared to the turned distant person situation can be explained by analysing the approaches horses showed towards the test persons without prior feeding from the buckets.…”
Section: Discussionmentioning
confidence: 99%
“…Lateralization may enable animals to concentrate on two tasks simultaneously such as foraging and predator vigilance (Rogers et al 2004). If lateralization initially evolved to cope with different information coming from each eye, resulting in left and right hemisphere specialization of information processing and a reduction of the potential negative effects of divided attention (Griffiths et al 2004), then variation in the level of exposure to predators may have affected the degree of specialization in the two brain hemispheres. Future studies using a detour test may help clarify this point further.…”
Section: Discussionmentioning
confidence: 99%